Agriculture, pesticide use, and economic development: A Global examination (1990-2014) - hedlund, J. , Longo, S.B. and York, R. (Rural Sociology)
Modern agricultural production typically requires large quantities of chemical pesticides, a potential source of both environmental and human harm. Previous social science research has suggested that environmental problems such as those associated with pesticide use may begin to decline at higher levels of economic development. Using fixed effects models, we examine whether this possible relationship holds within nations and over time. This study draws on data from the World Bank as well as pesticide use data from the Food and Agriculture Organization of the United Nations to examine the relationship between pesticide use and economic development within nations from 1990 to 2014. The findings are considered from theoretical perspectives in environmental sociology on the drivers of environmental impacts: the treadmill of production theory, structural human ecology, ecological modernization theory, and the environmental Kuznets curve hypothesis. The results of this study show a positive relationship between economic development and pesticide consumption over time, with no decline in use at higher levels of economic development. Thus, they generally support the claims made by treadmill of production and structural human ecology.- Reproduced